Pengaruh Kompetensi, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Bapenda Kabupaten Manggarai Barat dengan Sarana Prasarana sebagai Pemoderasi - Biyanto, Frasto; Setiawan Maini, Salesiana; Budiarto, Arief (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
This study aims to find out how the influence of competence, motivation, and work discipline on employee performance with infrastructure as a moderating variable. The method used in this research is quantitative. In this study, the population was employees of the West Manggarai Regency, East Nusa Tenggara, with a total of 45 respondents. The data processing technique in this study uses multiple linear regression analysis and Moderating Regression Analysis (MRA) with the SmartPLS 03 application. The results of the research conducted show that competency and work discipline variables have a positive effect on employee performance, motivational variables do not affect employee performance while competency, motivation and work discipline variables using facilities and infrastructure variables do not affect employee performance.